AUTHENTIC ASSESSMENT TEACHING AND LEARNING TRAJECTORY WITH E-STUDENT ACTIVITY SHEET (E-SAS) TO IMPROVE THE QUALITY OF LEARNING PROCESS - Herianingtyas, Nur Luthfi Rizqa; Rohman, Chaerul; Widiyanto, Rohmat; Amarulloh, Reza Ruhbani (JMIE (Journal of Madrasah Ibtidaiyah Education), 2023)
Traditional assessment in education primarily measures the academic performance of learners without reflecting the learning process. Many educators neglect to reflect on their teaching practices for continuous quality improvement. The authentic assessment instrument, Teaching and Learning Trajectory with E-Student Activity Sheet (E-SAS), can identify the profile of teaching and learning trajectories within the syntax of instructional models, enabling educators to determine appropriate corrective measures for each session. The development of this assessment instrument utilized the Research and Development (R&D) method, following the ADDIE model. The study involved 34 students enrolled in a Basic Science Concepts course. Fifteen authentic teaching and learning trajectory test items were developed for three sessions and were validated as "Valid" and achieved a "High" reliability category, with a Cronbach's Alpha reliability coefficient value of 0.68. The overall average student scores showed a significant improvement to 83.33 after the implementation of corrective actions. The quality of the learning process, employing Problem-Based Learning syntax, improved in each session following the educators' reflections based on the teaching and learning trajectory profiles.